Efektivitas Pembinaan Terkait Budidaya Tanaman Terhadap Produktivitas Dan Pendapatan Usahatani Kopi Di Desa Sumber Karya Kecamatan Gumay Ulu Kabupaten Lahat - Lukmanul Hakim (Universitas Bojonegoro, 2024)
Lahat Distirct is one of the largest coffee producers in Indonesia, which is precisely located in South Sumatra Province. Coffee is one of the plantation commodities which has an important role in economic activity in Indonesia. Coffee is a plantation crop that has been cultivated for a long time and is a commodity that makes a positive contribution to the trade balance for agricultural commodities. The role of coaching activities is needed to increase the productivity and income of coffee farmers. The purpose of this study was (1) to analyze and determine the differences in productivity between fostered coffee farmers and non-cultivated coffee farmers. (2) to analyze and find out the differences in income of fostered coffee farmers and non-coached coffee farmers. This research was conducted in Sumber Karya Village, Gumay Ulu Sub-District, Lahat Distict. Determination of the location of the study was done deliberately (purposive sampling location). The data collection of this research was conducted in August 2020. The data collected were primary data and secondary data. The research method used is a survey method. The results of the study can be concluded (1) The value of t-count> ttable means that Ho refusal is a significant difference between the productivity of fostered coffee farmers and non-fostered coffee farmers. (2) The value of t-count <t-table means that there is no significant difference in income between fostered coffee farmers and coffee farmers who are not coached. Development activities related to plant cultivation carried out in Sumber Karya Village have less positive impact on farmers due to the lack of improvement in terms of productivity, however, have a positive impact on the incomes of the fostered coffee farmers. This means that this coaching activity is less effective for farmers. This difference occurs because the results of coffee produced between fostered coffee farmers and coffee farmers who are not coached, cultivated coffee farmers produce organic robusta coffee, while coffee farmers who are not coached produce ordinary robusta coffee.